2017
DOI: 10.1080/19440049.2017.1310398
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulation of three plastic additives’ diffusion in polyethylene terephthalate

Abstract: Accurate diffusion coefficient data of additives in a polymer are of paramount importance for estimating the migration of the additives over time. This paper shows how this diffusion coefficient can be estimated for three plastic additives [2-(2'-hydroxy-5'-methylphenyl) (UV-P), 2,6-di-tert-butyl-4-methylphenol (BHT) and di-(2-ethylhexyl) phthalate (DEHP)] in polyethylene terephthalate (PET) using the molecular dynamics (MD) simulation method. MD simulations were performed at temperatures of 293-433 K. The dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 38 publications
1
3
0
1
Order By: Relevance
“…24,25 It can accurately simulate the free volume of the polymer system and the migration ability of the polymer chains. 8,26,27 The simulation results are highly consistent with the experimental values. 28 In this article, we found that EBO was an effective lubricant to strengthen the flowability of the ABS resin.…”
supporting
confidence: 80%
“…24,25 It can accurately simulate the free volume of the polymer system and the migration ability of the polymer chains. 8,26,27 The simulation results are highly consistent with the experimental values. 28 In this article, we found that EBO was an effective lubricant to strengthen the flowability of the ABS resin.…”
supporting
confidence: 80%
“…Due to the rapid advancement of computer simulation, molecular dynamics simulation (MD) has an extensive range of applications in guiding the design of high-performance composites [19,20]. It can accurately simulate the free volume of the polymer system and the migration ability of the polymer chains [21]. The simulation results are highly consistent with the experimental values.…”
Section: Introductionmentioning
confidence: 73%
“…In this work, all the molecular simulation processes were completed by Accelrys Material Studio (MS) 2017 [ 17 ]. The PET chain consisting of 100 repeat units [ 18 ] and CO 2 molecules were built by materials visualizer modules [ 19 ]. The cubic cells with two PET chains were constructed using an amorphous cell module, which is shown in figure 1 , and were subsequently equilibrated using the Forcite module.…”
Section: Computational Detailsmentioning
confidence: 99%